Eugenia cruciformis (Myrtaceae), a new species from the Western Ghats, India - Mani, Bince; Thomas, Sinjumol (Phytotaxa, 2025)
The new species, Eugenia cruciformis is described from the southern Western Ghats, India. The species is easily distinguishable from other Eugenia species in the region by the notably distinctive cruciform shape of its staminal disc. A detailed description, illustrations, photographs, phenology and comparison of diagnostic characters with morphologically similar species are provided.